Packet Size Optimization Techniques and Challenges for Wireless Body Area Networks: Enhancing Energy Efficiency and Communication Performance in Wireless Body Area Networks (Journal of Advances and Scholarly Researches in Allied Education, 2018)
As of late, Wireless Body Area Network (WBAN) has attracted huge enthusiasm to numerous analysts because of its potential in medicinal services and therapeutic fields. In this paper, we propose the vitality productivity model of Time Diversity correspondence in Rician and Rayleigh blurring channels stressing the ideal packet size. The ideal packet size to amplify vitality effectiveness is explored for on-body and in-body channels. Four regulation systems are considered including the as of late proposed 16-ary Quadrature Amplitude Position Modulation (QAPM). What's more, the shut structure articulation of the vitality effectiveness model in multipath blurring is inferred. Here, three assessment measurements including the vitality productivity, the standardized throughput and the normal start to finish delay are embraced and contrasted with the current 1-bounce and Cooperative correspondences just as our recently proposed 2-jump correspondence. The outcomes show that our proposed Time Diversity correspondence plot outflanks the current ones in profound blurring channel aside from the normal start to finish delay.